2007
DOI: 10.1029/2006wr005333
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional characterization of hydraulic heterogeneity by multiple pumping tests

Abstract: [1] The conventional analysis of pumping tests by type-curve methods is based on the assumption of a homogeneous aquifer. Applying these techniques to pumping test data from real heterogeneous aquifers leads to estimates of the hydraulic parameters that depend on the choice of the pumping and observation well positions. In this paper, we test whether these values may be viewed as pseudo-local values of transmissivity and storativity, which can be interpolated by kriging. We compare such estimates to those obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 44 publications
(96 reference statements)
1
81
0
Order By: Relevance
“…The high storage coefficients may be an indication of contact with another aquifer layer and thus a water source between the wells, or they may be the result of vertical cross-flow in the observation wells. In this case, however, they are probably the result of overfitting due to unresolved spatial heterogeneity (Li et al 2007). The permeability between Ktzi 200 and Ktzi 201 shows values between 166 and 431 mD, which is significantly greater than the mean aquifer permeability.…”
Section: Cross-hole Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high storage coefficients may be an indication of contact with another aquifer layer and thus a water source between the wells, or they may be the result of vertical cross-flow in the observation wells. In this case, however, they are probably the result of overfitting due to unresolved spatial heterogeneity (Li et al 2007). The permeability between Ktzi 200 and Ktzi 201 shows values between 166 and 431 mD, which is significantly greater than the mean aquifer permeability.…”
Section: Cross-hole Observationsmentioning
confidence: 99%
“…Several methods exist for the identification of spatial structures and variability (e.g. Vasco et al 2000, Vasco et al 2001, Li et al 2007, Wiese and Nützmann 2008. However, these approaches were designed to analyse large datasets and do not permit the evaluation of single-hole tests.…”
Section: Instrumentationmentioning
confidence: 99%
“…A second group of methods estimates a single best solution that captures some of the details at smaller scales, namely those which are important for groundwater flow and transport predictions, and also estimates an uncertainty associated with the prediction [e.g., Hernandez et al, 2003;Vermeulen et al, 2004;Tonkin and Doherty, 2005;Tonkin et al, 2007]. Often, the calibration focuses on the uncertain hydraulic conductivities, but sometimes also other parameters like the storativities [Hendricks Franssen et al, 1999;Li et al, 2007] or recharge rate [Hendricks Franssen et al, 2004 are subject to calibration. Only rarely, like in the Representer Method [Bennett, 1992;Valstar, 2001] the uncertainty of the model itself is considered.…”
Section: Motivationmentioning
confidence: 99%
“…They include numerical studies [e.g., Gottlieb and Dietrich, 1995;Yeh and Liu, 2000;Bohling et al, 2002;Yeh, 2005, 2006;Fienen et al, 2008;Ni and Yeh, 2008;Castagna and Bellin, 2009;Xiang et al, 2009;Liu and Kitanidis, 2011], followed by laboratory sandbox studies [e.g., Liu et al, 2002;Brauchler et al, 2003;Illman et al, 2007;Liu et al, 2007;Illman et al, 2008;Yin and Illman, 2009;Illman et al, 2010;Berg and Illman, 2011a;Illman et al, 2012] and then experimental field studies [e.g. Bohling et al, 2007;Li et al, 2007;Straface et al, 2007;Cardiff et al, 2009;Illman et al, 2009;Berg and Illman, 2011b;Brauchler et al, 2011;Huang et al, 2011]. All these studies have consistently shown that transient HT can identify not only the pattern of the heterogeneous hydraulic conductivity field but also the variation of specific storage.…”
Section: Introductionmentioning
confidence: 99%